INOVASI MEDIA EDUBUTTERFLY BERBASIS PROYEK DALAM MENINGKATKAN PEMAHAMAN KEGIATAN EKONOMI SISWA SEKOLAH DASAR - Tri Enjeli, Farizka; Widiana Rahayu, Dewi; Thamrin Hidayat, Muhammad; Wahyudi, Agus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the low learning outcomes of fourth-grade elementary students in understanding economic activities, particularly production, distribution, and consumption, due to the use of conventional and less interactive learning media. The purpose of this study is to determine the effectiveness of EduButterfly media based on Project-Based Learning (PjBL) in improving students’ learning outcomes. This research employs a Research and Development (R&D) approach using a One Group Pretest-Posttest design. The subjects of this study were fourth-grade students at SDN Kedungdoro 2 Surabaya. Data were collected through tests (pretest and posttest) and student response questionnaires. The results show a significant improvement in students’ learning outcomes, as indicated by the increase in posttest scores compared to pretest scores and supported by the N-Gain results in the moderate to high category. In addition, student responses toward the use of EduButterfly media were very positive, indicating that the media is engaging, interactive, and effective in facilitating learning. Therefore, the EduButterfly media based on Project-Based Learning is proven to be effective in improving students’ understanding of economic activity materials in elementary school.